The causal relationship between sarcopenic obesity factors and benign prostate hyperplasia - Rao, Xuezhi; Xu, Zhijie; Zhang, Jingchun; Zhou, Jiaxiang; Huang, Jian; Toh, Zhanhao; Zheng, Ruwen; Zhou, Zhiyu (Frontiers in Endocrinology, 2023)
Both benign prostatic hyperplasia (BPH) and sarcopenic obesity (SO) are common conditions among elderly males. The prevalent lifestyle associated with SO is a significant risk factor for the development of BPH. Therefore, we investigated the causal relationship between SO factors and BPH.The instrumental variables for SO factors were selected using the inverse varianceweighted method, which served as the primary approach for Mendelian randomization analysis to assess the causal effect based on summary data derived from genome-wide association studies of BPH.The increase in BMR (OR = 1.248; 95% CI = (1.087, 1.432); P = 0.002) and ALM (OR = 1.126; 95% CI = (1.032, 1.228); P = 0.008) was found to be associated with an elevated risk of BPH. However, no genetic causality between fat-free mass distribution, muscle mass distribution, and BPH was observed.Our findings indicate that a genetic causal association between BMR, ALM and BPH.BMR and ALM are risk factors for BPH. The decrease in BMR and ALM signified the onset and progression of SO, thus SO is a protective factor for BPH.